Cold Case Homicides: DNA Testing of Retained Autopsy Sexual Assault Smears. Issue 4 (7th February 2019) - Clark, Michelle; Gill, James; Sasinouski, Kristin; McGuire, Angela
Abstract: Archival medical examiner specimens may contain perpetrator DNA evidence useful in unsolved ("cold case") homicides. The Office of the Chief Medical Examiner (OCME) histology slide archives were searched for sexual assault smears for all 376 female homicides from 1990 to 1999. Of these, the OCME had sexual assault smears on 84 of which 13 slides had sperm. Of these 13, six were still unsolved. DNA profiles were obtained on all six (5 from smears and one from swabs). Combined DNA Index System ( submission resulted in two matches ("hits") for new suspects. In addition, three suspects were eliminated in two cases. Our review of archival sexual assault smears resulted in DNA profiles that were able to assist in the investigation of four cold case homicide investigations. It may be worthwhile for medical examiner offices to search their archival histology slides for sexual assault smears on previously unsolved cases particularly those prior to the mid‐1990s when DNA testing was less widely available.